Administration of watermelon rind powder to Nile tilapia (Oreochromis niloticus) culture under biofloc system: Effect on growth performance, innate immune response, and disease resistance - Hien Van Doan (2020)
© 2020 Elsevier B.V. An eight-week experiment was performed to assess the effectiveness of watermelon rind powder (WMRP) on growth efficiency, immunity, and disease resistance of Nile tilapia, O. niloticus. Three hundred fish (17.14 ± 0.12 g) were fed five diets; 0 (Diet 1- control), 20 g kg−1 WMRP (Diet 2), 40 g kg−1 WMRP (Diet 3), 80 g kg−1 WMRP (Diet 4), and 160 g kg−1 WMRP (Diet 5). Growth parameters, skin mucus, and serum immunities were analyzed after four and eight weeks of feeding. After eight weeks of the feeding, ten fish were used in the challenge against Streptococcus agalactiae over 15 days. Statistically significant enhancement (P ≤.05) of skin mucus and serum immune parameters were revealed through the WMRP feeding vs. control fed fish, in which the maximum (P ≤.05) enhancement of immune parameters was detected in tilapia fed the 40 g kg−1 WMRP diet, followed by the 20, 80, and 160 g kg−1 WMRP diets. Relative percent survival (RSP) in the challenge study of fish fed 20, 40, 80, and 160 g kg−1 WMRP was 57.14%, 76.19%, 61.90%, and 52.38%, respectively. The growth parameters were statistically (P ≤.05) enhanced in the WMRP feedings, in which the largest increase was revealed in the 40 g kg−1 WMRP treatment. In summary, the 40 g kg−1 WMRP additive increased both the growth efficiency and health status of Nile tilapia.